Analisis Customer Experience terhadap Minat Berkunjung Kembali pada Obyek Wisata Kabupaten Lembata - Nazarudin, Hamzah; Indawati J Nino; Tantri Widiastuti (Jurnal Ilmiah Aset, 2025)
The purpose of this research is to determine the influence of customer experience (education value, aesthetics value, entertainment value, escapism value) on the intention to revisit tourist attractions in Lembata Regency. The respondents in this study were 100 tourists who visited tourist attractions in Lembata Regency. The sampling technique used was non-probability sampling with the purposive sampling method, where samples were selected based on specific criteria, including: a. Respondents who had visited tourist attractions in Lembata Regency at least twice, b. Respondents aged over 20 years, as at this age, they are expected to have the ability to assess and understand the research variables. The data analysis technique used in this study was multiple linear regression analysis. The results of the study indicate that customer experience, consisting of education value, aesthetics value, entertainment value, and escapism value, has a positive influence both partially and simultaneously on the intention to revisit tourist attractions in Lembata Regency. Based on the coefficient of determination (R-square) of 0.573 (0.573 x 100) = 57.3%, it shows that customer experience can explain 57.3% of the intention to revisit tourist attractions in Lembata Regency, while the remaining 42.7% is influenced by other variables.